Advancing SDGs-oriented Science Learning through Ethno‑STEAM‑PjBL: An Integrative Review of Scientific Literacy and Environmental Attitudes - Firman Mohamad Rizky; Asri Widowati; Sabar Nurohman; Winarto (Jurnal Penelitian Pendidikan IPA, 2026)
This integrative literature review examines how Ethno‑STEAM integrated with Project‑Based Learning (Ethno‑STEAM‑PjBL) supports scientific literacy and environmental attitudes in science education. Literature was collected from Google Scholar, SINTA-indexed journals, Scopus, and ERIC databases using keywords related to ethnoscience, Ethno‑STEAM, Project‑Based Learning, scientific literacy, environmental attitudes, and science education. Sixteen empirical studies published between 2017 and 2025 were selected based on predefined inclusion and exclusion criteria and analyzed using narrative thematic synthesis. The findings revealed four major themes. First, Ethno‑STEAM‑PjBL is characterized by authentic cultural contexts, interdisciplinary integration, project-based learning, and active student participation. Second, scientific literacy outcomes consistently improved, with reported N‑gain values ranging from 0.20 to 0.71 and significant intervention effects (p < 0.05) in several studies. Third, environmental attitudes improved from moderate to high categories, with reported gains including n‑Gain values of 0.38 and significant improvements in ecological attitude measures (p < 0.001). Fourth, the synthesis identified five SDGs-oriented instructional design principles: contextualization, interdisciplinary integration, project orientation, sustainability orientation, and student agency. Overall, the evidence suggests that Ethno‑STEAM‑PjBL provides a promising framework for contextual and sustainability-oriented science learning by simultaneously strengthening scientific literacy, environmental responsibility, and SDGs-related competencies.